(untitled) (Herald of Journalism, 2016)
The peculiarities of the broadcast Love radio in Kazakhstan, Russian and Kazakh components Love radio. The author studies the uniqueness of image advertising Love radio, promoting and maintaining a positive image in the eyes of radio listener and especially the perception of radio audience.